Incidence and prevalence of intravenous medication errors in the UK: a systematic review. Issue 1 (23rd October 2018) - Sutherland, Adam; Canobbio, Michela; Clarke, Janine; Randall, Michelle; Skelland, Tom; Weston, Emma
Abstract : Objectives: Medication error is the most common type of medical error, and intravenous medicines are at a higher risk as they are complex to prepare and administer. The WHO advocates a 50% reduction of harmful medication errors by 2022, but there is a lack of data in the UK that accurately estimates the true rate of intravenous medication errors. This study aimed to estimate the number of intravenous medication errors per 1000 administrations in the UK National Health Service and their associated economic costs. The rate of errors in prescribing, preparation and administration, and rate of different types of errors were also extracted. Methods: MEDLINE, Embase, Cochrane central register of clinical trials, Database of Abstracts of Reviews of Effectiveness, National Health Service Economic Evaluation Database and the Health Technology Appraisals Database were searched from inception to July 2017. Epidemiological studies to determine the incidence of intravenous medication errors set wholly or in part in the UK were included. 228 studies were identified, and after screening, eight papers were included, presenting 2576 infusions. Data were reviewed and extracted by a team of five reviewers with discrepancies in data extraction agreed by consensus. Results: Five of eight studies used a comparable denominator, and these data were pooled to determine a weighted mean incidence of 101 intravenous medication errors per 1000 administrations (95% CI 84 to 121). Three studies presented prevalence data but these were based on spontaneous reports only; therefore it did not support a true estimate. 32.1% (95% CI 30.6% to 33.7%) of intravenous medication errors were administration errors and 'wrong rate' errors accounted for 57.9% (95% CI 54.7% to 61.1%) of these. Conclusion: Intravenous medication errors in the UK are common, with half these of errors related to medication administration. National strategies are aimed at mitigating errors in prescribing and preparation. It is now time to focus on reducing administration error, particularly wrong rate errors.